The Existence of Lao Proverbs in Lao Modern Society - HAIBIN, SU (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
Researching the persistence of proverbs in current Lao society, which has two objectives: to analyze the distribution of proverbs in current Lao society and the presentation of proverbs in current textbooks. The study is based on the theory of traditional proverb dissemination style of He Chi Ran (2014:11) as a guide to analyze the study results as follows: There are 4 ways of publishing proverbs in Lao society today: written proverbs with pictures, proverbs with pictures, proverbs with lines, proverbs with interpretations. Among them, proverbs written with pictures and proverbs published with comparative pictures; Proverb style with pictures Found to publish proverbs with picture metaphors that are reminders in living; Proverbs with line drawing. Find a published model with line drawing to help improve children's cognitive development; the style of publication with the interpretation of proverbs. The style of presentation with the interpretation of proverbs is a column of proverbs on the newspaper page.